STRATEGI PEMBELAJARAN PAIKEM PADA PELAJARAN PAI UNTUK MENINGKATKAN MOTIVASI DAN MINAT BELAJAR SISWA - Hani Nurulhanifah; Muhammad Hisyam Iskandar; Hani Siti Nuraeni; Rismayanti; Fiqra Muhamad Nazib (Advances In Education Journal, 2025)
This study aims to analyze the literature on the PAIKEM Strategy in Islamic Religious Education Lessons. The study uses a Systematic Literature Review approach with the stages of determining the theme, searching, selecting literature, analyzing, compiling drafts, and disseminating the results. The study used 16 articles from the selection of 30 articles obtained from various sources with publication years from 2019-2024. The focus of the research is on 3 themes, namely implementation, evaluation and implications of using the PAIKEM strategy in Islamic Religious Education lessons. The results of the study show that: 1) The implementation of the PAIKEM Strategy in Islamic Religious Education learning is carried out with various interesting learning models and learning media. 2) The results of the evaluation of the Implementation of the PAIKEM Strategy in Islamic Religious Education learning resulted in a good improvement in the learning process. 3) The implementation of the PAIKEM Strategy in Islamic Religious Education learning has a positive impact on the learning process, namely providing student motivation, providing a pleasant and interesting atmosphere for students and making it easier for teachers to deliver material.